Domestic Abuse in the Context of Life-Limiting Illness: A Systematic Scoping Review. (10th April 2023) - Myall, Michelle; Taylor, Sophia; Wheelwright, Sally; Lund, Susi
Abstract : Domestic abuse is a worldwide public health and social issue which impacts the health and wellbeing of those experiencing abuse and their families. People living with a life-limiting illness are at increased risk of domestic abuse because they are often frail, isolated, and dependent on others. Little is known about domestic abuse and the coexistence of life-limiting illness and existing support for those experiencing or at risk of abuse. A scoping review was conducted to identify factors that shape and characterise experiences of adults with a life-limiting illness affected by domestic abuse and the health and social care practitioners and other organisations that support them. The Joanna Briggs Institute (JBI) methodology and checklist for Preferred Reporting Items for Systematic Reviews and Meta Analyses-Extension for Scoping Reviews (PRISMA-ScR) were applied. Five databases were systematically searched from 2000 to 2021: MEDLINE; CINAHL; PsycINFO; Social Sciences Citation Index (Web of Science); and ProQuest Dissertations and Global. Twenty-one papers met the inclusion criteria. Most studies were conducted in North America, with female participants living with cancer, and conducted in health and community settings. There were no studies involving third sector organisations. A range of abusive behaviours was reported resulting in missed medical appointments, delays in screening leading to late diagnosis, and palliative rather than curable treatment. Abuse also impacted on the physical, emotional, and psychological wellbeing of the person experiencing the abuse, which increased stress levels and could have a detrimental effect on their health. Identifying domestic abuse within the context of life-limiting illness was reported to be challenging for health and social care professionals, as was responding to and managing a disclosure. Further research is needed to address existing knowledge in order to inform policy and practice to identify and manage domestic abuse where it coexists with life-limiting illness.